Citation practices in tourism research: Toward a gender conscientious engagement. - Nunkoo, Robin; Hall, C. Michael; Rughoobur, Soujata; Teeroovengadum, Viraiyan (2019)
This study explores gender gaps and differences in citation practices of scholars in the top-cited articles in tourism research. The results suggest that male researchers dominate the authorship of those articles and are more likely to engage in self-citation than females. The study also finds a disparity in citation counts between male- and female-authored articles. Controlling for other factors, author gender is an important determinant of citation counts. The study advocates for a more gender conscious citation practices and provides potential gender-based interventions to reduce the citation gap. The research raises awareness about the dangers of the perfunctory use of citations and paves the way for further debates on the politics and embedded inequalities of citations in tourism research.